Establishing Design Criteria for Hobby Garden Huts: A Case Study at Selcuk University - Ali AKCAOVA; Ahmet AKAY (JES: Journal of Engineering Sciences)
This study aims at developing standardized design criteria for the hobby gardens at Selçuk University, ensuring compatibility with environmental conditions, enhancing aesthetic value, prioritizing user satisfaction, and catering specifically to the institution's context. The study was conducted within the hobby garden in the Alaeddin Keykubat campus of Selçuk University. The extant parcels in the hobby garden have 70 m2 of open space for the landscape design area and 20 m2 of semi-open and closed space on hard ground for the hut design area. Two distinct questionnaires were utilized in the study. In the initial phase, a preliminary test was conducted, with the involvement of design professionals. In this preliminary stage, 30 huts previously designed by experts were presented to a panel of professionals for their opinion on various criteria such as color, material and form, and the 15 huts with the highest scores were selected. A questionnaire was then administered to the existing users of the hobby garden through the identified huts. The aim of this questionnaire is to determine the hut design criteria. Based on these criteria, the 2 most successful hut designs in terms of spatial quality and social cohesion were determined. The data collected were subsequently analyzed using the SPSS statistical software. The study employed the psychometric measurement method. The survey was designed using a 5-point Likert-type measurement model, in which 1 denotes a negative value and 5 a positive one. The study used the independent t-test, frequency analysis, normality test, and Cronbach Alpha reliability analysis.